Thibetana keili Efetov & Tarmann, a new species of the genus Thibetana Efetov & Tarmann, 1995, from Tibet (Lepidoptera: Zygaenidae, Procridinae, Artonini) - K. A. Efetov; G. M. Tarmann (SHILAP)
A new species, Thibetana keili Efetov & Tarmann, sp. n., is described from Tibet (China). The characters of this species are compared with those of Artona postalba Elwes, 1890 (from Sikkim, India). The latter species is transferred here from Artona Walker, 1854, to Thibetana Efetov & Tarmann, 1995: Thibetana postalba (Elwes, 1890), comb. n. Moreover, also Artona zebra Elwes, 1890 (from Sikkim, India) is here transferred from Artona to Thibetana: Thibetana zebra (Elwes, 1890), comb. n.